The experience of assessing and adapting trauma-informed sport programs in a national community organization. - Shaikh, Majidullah; Bergholz, Lou; Scott, Bruce; Rojas, Maren; Bean, Corliss; Forneris, Tanya (Université d'Ottawa | University of Ottawa, 2019)
Youth from disadvantaged circumstances (e.g., low socioeconomic status, from under-resourced communities) are disproportionately at risk to exposure to traumatic experiences, such as family violence, abuse, and neglect. Left untreated, these experiences can lead to cognitive and emotional dysregulation and impairments to social relatedness. With the popularity of sport as an avenue for engaging youth, sport program leaders can be trained in trauma-informed approaches that leverage sport as an opportunity to build youth resilience: the ability to overcome adverse experiences and orient oneself toward healing. The purpose of this study was two-fold: (a) to explore the implementation experiences of the pilot phase of trauma-informed sport programming in a national community organization that serves at-risk youth and (b) understand the knowledge gained from this implementation that can inform program expansion. The pilot phase of program implementation involved having twelve program leaders (i.e. supervisors, managers, and coaches) from three sites attend three two-day training workshops throughout the development and implementation of the trauma-informed sport programming to youth aged 8-12 years old at their respective sites. Data were collected from program leaders through interviews, focus groups, and program observations during the 1-year pilot study. The data analysis drew upon personal narratives of the leaders along with themes that were constructed from the program leaders’ shared experiences. Results indicate that program successes (e.g., staff training, session delivery, youth receptivity) were limited by program constraints (e.g., recruitment, retention, staff inconsistency). These results then helped inform proposed refinements to programming (e.g., greater program lengths), and proposed solutions for expansion (e.g., training peer facilitators, integration with existing programming). Study implications shed light on the strengths and challenges in program implementation, and how this knowledge can be used to improve current practices of program leaders and optimize the processes and impact of trauma-informed sport programming for youth.
Keywords: trauma-sensitive; partnership; community-engaged; resilience; coach learning